Studi Komparasi Teknik Marmet Dan Pijat Oksitosin Terhadap Produksi Asi Pada Ibu Post Partum Primipara Di Rumah Sakit Wilayah Daerah Istimewa Yogyakarta - Benny Karuniawati; Erma Nur Fauziandari; Amri Wulandari (Jurnal Kesehatan Karya Husada, 2014)
Exclusive breastfeeding is an important but challenging program as it’s associated with varied social issues among Indonesian people. In 2012, only 48% of mothers in Special Distric of Yogyakarta participated in exclusive breastfeeding program showing a decrease compared to previous year achievement. This may be caused by several factors including, baby’s difficulty in sucking the milk, severe nipple pain preventing the mothers to breast feed their babies, and low breast milk production among post partum primipara mothers. Several techniques have been introduced to increase breast milk production including Marmet technique and oxytocin massage, which are shown to be effective among post section caesario mothers. This study aimed to observe the efficiency of the Marmet technique and oxytocin massage among post partum primipara per vagina mothers. A number of 29 participants were grouped into Marmet technique threatment (ten participants), oxytocin massage threatment (ten participants), and control group with no threatment (nine participants). Post test only with non equivalent control group were used in this study to indirectly estimate breast milk production by measuring the newborn babies’ weight at their first week age. Baby’s weight decrease that is less than 10% indicated sufficient breast milk production. The measurement was performed only once at post threatment period. The results shown that 90.9% mothers in the first group (oxytocin massage treatment) have sufficient breast milk production, 100% mothers in the second group (Marmet technique) have sufficient breast milk production, and only 25% mothers in the control group have sufficient breast milk production. Statictical analysis shown no difference (p = 0.496) between Marmet technique and oxytocin massage.